Mechanical Stimulation (Pulsed Electromagnetic Fields “PEMF” and Extracorporeal Shock Wave Therapy “ESWT”) and Tendon Regeneration: A Possible Alternative - Rosso, Federica; Bonasia, Davide E.; Marmotti, Antonio; Cottino, Umberto; Rossi, Roberto (Frontiers in Aging Neuroscience, 2015)
The pathogenesis of tendon degeneration and tendinopathy is still partially unclear. However, an active role of metalloproteinases (MMP), growth factors, such as vascular endothelial growth factor (VEGF) and a crucial role of inflammatory elements and cytokines was demonstrated. Mechanical stimulation may play a role in regulation of inflammation. In vitro studies demonstrated that both pulsed electromagnetic fields (PEMF) and extracorporeal shock wave therapy (ESWT) increased the expression of pro-inflammatory cytokine such as interleukin (IL-6 and IL-10). Moreover, ESWT increases the expression of growth factors, such as transforming growth factor β(TGF-β), (VEGF), and insulin-like growth factor 1 (IGF1), as well as the synthesis of collagen I fibers. These pre-clinical results, in association with several clinical studies, suggest a potential effectiveness of ESWT for tendinopathy treatment. Recently PEMF gained popularity as adjuvant for fracture healing and bone regeneration. Similarly to ESWT, the mechanical stimulation obtained using PEMFs may play a role for treatment of tendinopathy and for tendon regeneration, increasing in vitro TGF-β production, as well as scleraxis and collagen I gene expression. In this manuscript the rational of mechanical stimulations and the clinical studies on the efficacy of extracorporeal shock wave (ESW) and PEMF will be discussed. However, no clear evidence of a clinical value of ESW and PEMF has been found in literature with regards to the treatment of tendinopathy in human, so further clinical trials are needed to confirm the promising hypotheses concerning the effectiveness of ESWT and PEMF mechanical stimulation.